Избранное - Гумилев Николай Степанович (Библиотека словесника, 1990)
Экземпляры: ф.3 (1991) / Инвентарный номер: 33466 / Цена: / Сис.шифр: 84(2Рос=Рус) / Авт.знак: Г 94 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)